On-Surface Synthesis of Single-Layered Two-Dimensional Covalent Organic Frameworks via Solid–Vapor Interface Reactions - Liu, Xuan-He; Guan, Cui-Zhong; Ding, San-Yuan; Wang, Wei; Yan, Hui-Juan; Wang, Dong; Wan, Li-Jun (Journal of the American Chemical Society, 2013)
Surface covalent organic frameworks (SCOFs), featured by atomic thick sheet with covalently bonded organic building units, are promised to possess unique properties associated with reduced dimensionality, well-defined in-plane structure, and tunable functionality. Although a great deal of effort has been made to obtain SCOFs with different linkages and building blocks via both “top-down” exfoliation and “bottom-up” surface synthesis approaches, the obtained SCOFs generally suffer a low crystallinity, which impedes the understanding of intrinsic properties of the materials. Herein, we demonstrate a self-limiting solid–vapor interface reaction strategy to fabricate highly ordered SCOFs. The coupling reaction is tailored to take place at the solid–vapor interface by introducing one precursor via vaporization to the surface preloaded with the other precursor. Following this strategy, highly ordered honeycomb SCOFs with imine linkage are obtained. The controlled formation of SCOFs in our study shows the possibility of a rational design and synthesis of SCOFs with desired functionality.